Doctrine clerics and the colonial economy (Lima, 1600-1630) - Acosta, Antonio (1982)
It does not seem an exaggeration to say that, in relation to other parts of the colonial history of Hispanic America, the one that corresponds to the role of the Church is today one of the least known. Referring specifically to Peru, the available knowledge consists, fundamentally, of an empirical base contained in several collections of documents, important as a starting point; next to it, some general or particular stories; and, finally, a still small number of problem analyses.